Biocompatible Organic Electronics: Dibenzoindigo: A Nature‐Inspired Biocompatible Semiconductor Material for Sustainable Organic Electronics (Advanced Optical Materials 9/2017). Issue 9 (May 2017) - Leshanskaya, Lidiya I.; Klimovich, Irina V.; Dashitsyrenova, Dolgor D.; Frolova, Lyubov A.; Ershova, Elizaveta S.; Sergeeva, Vasilina A.; Tabakov, Vyacheslav Yu.; Kostyuk, Svetlana V.; Lyssenko, Konstantin A.; Troshin, Pavel A.
Abstract : Blue colorant indigo, occurring in Indigofera tinctoria plant, attracts much attention as ambipolar semiconductor designed by nature. In article number1601033, Pavel A. Troshin and co‐workers present a nature‐inspired material dibenzoindigo, which shows remarkably improved electrical performance compared to parent indigo and also excellent ambient and photostability. Biological assays reveal that dibenzoindigo positively influences proliferation of human cells, which paves a way towards an extensive application of this material in biocompatible electronics.